Rs aggarwal solutions
Our top 5% students will be awarded a special scholarship to Lido.

Factorization of Polynomials | Factorization of Polynomials Exercise 3F

Question 36

(𝑥 + 2)^3 − (𝑥 − 2)^3

Looking to do well in your science exam ?  
Learn from an expert tutor. Book a free class!

(𝑥 + 2)^3 − (𝑥 − 2)^3

According to the equation,

𝑎^3 − 𝑏^3 = (𝑎 − 𝑏)(𝑎^2 + 𝑎𝑏 + 𝑏^2)

So we get,

= ((𝑥 + 2) − (𝑥 − 2))((𝑥 + 2)^2 + (𝑥 + 2)(𝑥 − 2) + (𝑥 − 2)^2)

= (𝑥 + 2 − 𝑥 + 2)( (𝑥 + 2)^2 + (𝑥^2 − 2^2) + (𝑥 − 2)^2)

According to the equation,

(𝑎 + 𝑏)^2 = 𝑎^2 + 2𝑎𝑏 + 𝑏^2

(𝑎 − 𝑏)^2 = 𝑎^2 − 2𝑎𝑏 + 𝑏^2

So we get,

= 4((𝑥^2 + 2(𝑥)(2) + 2^2) + 𝑥^2 − 2^2 + (𝑥^2 − 2(𝑥)(2) + 2^2))

= 4(𝑥^2 + 4𝑥 + 4 + 𝑥^2 − 4 + 𝑥^2 − 4𝑥 + 4)

= 4(3𝑥^2 + 4)

Set your child up for success with Lido, book a class today!

Our top 5% students will be awarded a special scholarship to Lido.

subject-cta

Question 36

(𝑥 + 2)^3 − (𝑥 − 2)^3

Looking to do well in your science exam ? Learn from an expert tutor. Book a free class!

(𝑥 + 2)^3 − (𝑥 − 2)^3

According to the equation,

𝑎^3 − 𝑏^3 = (𝑎 − 𝑏)(𝑎^2 + 𝑎𝑏 + 𝑏^2)

So we get,

= ((𝑥 + 2) − (𝑥 − 2))((𝑥 + 2)^2 + (𝑥 + 2)(𝑥 − 2) + (𝑥 − 2)^2)

= (𝑥 + 2 − 𝑥 + 2)( (𝑥 + 2)^2 + (𝑥^2 − 2^2) + (𝑥 − 2)^2)

According to the equation,

(𝑎 + 𝑏)^2 = 𝑎^2 + 2𝑎𝑏 + 𝑏^2

(𝑎 − 𝑏)^2 = 𝑎^2 − 2𝑎𝑏 + 𝑏^2

So we get,

= 4((𝑥^2 + 2(𝑥)(2) + 2^2) + 𝑥^2 − 2^2 + (𝑥^2 − 2(𝑥)(2) + 2^2))

= 4(𝑥^2 + 4𝑥 + 4 + 𝑥^2 − 4 + 𝑥^2 − 4𝑥 + 4)

= 4(3𝑥^2 + 4)

Our top 5% students will be awarded a special scholarship to Lido.

subject-cta
Connect with us on social media!
2021 © Quality Tutorials Pvt Ltd All rights reserved
`